Utilization of The Sahehly Application as a Learning Media for Arabic Writing - Wati, Mahrida; Ahmed, Bakri Mohamed Bkheet (UIN ANTASARI, 2023)
The development of digital technology in the 5.0 era provides solutions in overcoming various kinds of problems in the world of education, one of which is the problem in Imla learning. Imla is a branch of Arabic science that studies the rules of writing Arabic. In practice, the material in Imla lessons is expected to be more effective and efficient by using learning media. Through the Sahehly application, imla's learning and teaching activities become easier for both teachers and students. The purpose of this study was to find out the use of the Sahehly application as a learning media for Imla at Pondok Darul Hijrah Putri. The research design used is descriptive qualitative. The informants in this study were 1 (one) Imla teacher. Data collection methods carried out by researchers are through interviews, observation, and documentation. The results of this study indicate that the use of the Sahehly application as Imla learning media makes it easier for teachers to correct students' writing by using features in the application such as feature ibda’ at-tashhih, tasykil an-nash, and tadqiq imla'i wa nahwi.